Pengaruh Kepemimpinan dan Iklim Organisasi Terhadap Kinerja Karyawan pada PT. HM Sampoerna Tbk Padang - Amelia, Rizki; Bakkareng, Bakkareng; Begawati, Nova (Fakultas Ekonomi, Universitas Ekasaktii, 2024)
This study aims to examine and analyze the influence of leadership and organizational climate on employee performance at PT. HM Sampoerna Tbk, Padang where the variable X is leadership and organizational climate. Dependent variable is employee performance. The study population was 184 and a sample of 98 respondents. This study used a classical assumption test consisting of normality test, multiculity test, herosadicity test and multiple regression test, t test and F test. Results of the research variable leadership has a positive and insignificant effect on employee performance at PT. HM Sampoerna Tbk Padang, the organizational climate variable has a positive and significant effect on employee performance at PT. HM Sampoerna Tbk Padang and leadership variables and organizational climate together or simultaneously have a significant and significant effect on employee performance at PT. HM Sampoerna Tbk Padang.